KAMPUNG-KAMPUNG BERSEJARAH DI KOTA SEMARANG: Kajian Atas Nama Tempat - Hendro, Eko Punto (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
As the pre-industrial city, Semarang in the early days of developing traditional, centered on residential Regent (Kanjengan), mosques and squares surrounded by township residents that were grouped on the basis of occupation, race, ethnicity, religion and profession. Entering the 19th century, the city of Semarang grew following the planning concepts and structure of modern (Western) style, namely as an industrial city, with the characteristics and patterns different from the traditional city. As a modern city Semarang rests on the modern street system. Until recently the township-village still exists in the city, although not functioning as before.